A Survey on Work-related Musculoskeletal Disorders (WMSDs) among Construction Workers - Isa, Halim; Rohana, Abdullah (National Institute of Occupational Safety and Health, 2012)
Work-related Musculoskeletal Disorders (WMSDs) are common occupational injuries among workers in the construction industry. Epidemiological studies indicated that WMSDs include neck pain, lower back pain, knee pain, leg fatigue as well as ankle and feet discomfort. The objectives of this study are to identify the WMSDs experienced by the workers during construction works and discuss the causes of those WMSDs. Subjective approach associated with modified Nordic Musculoskeletal Questionnaire (NMQ) was applied to identify the symptoms of WMSDs. A case study was conducted in several construction sites situated at the southern region of Peninsular Malaysia. During the study, 37 construction workers with different age and scope of works were interviewed to determine the WMSDs that they have experienced. Based on distributed questionnaire, almost all workers experienced pain in the region of lower back, upper back and biceps. These pains were contributed by manipulation of heavy load and high force exertion. Based on discussed causations, control measures via engineering controls method and administrative controls method were proposed to alleviate the risk of WMSDs among construction workers.